The REFORMASI KURIKULUM DALAM KONTEKS DESENTRALISASI: ANALISIS KRITIS TERHADAP TIGA STUDI TERKAIT - -, bunyamin_unnes; Handoyo, Eko; Rokhman, Fathur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Curriculum change responds to global challenges and local demands for improving education quality. In Indonesia, the Merdeka Curriculum reflects a reform initiative focusing on flexibility, differentiated learning, and the development of character and 21st-century competencies. However, its implementation faces various obstacles, particularly within decentralized education systems. This study aims to critically examine curriculum change dynamics using a qualitative approach through a literature review method. Three core articles were analyzed: ICT and Curriculum Change (Voogt & Pelgrum, 2005), Curriculum Reform in Indonesia (Simarmata & Mayuni, 2023), and Curriculum Reform in the Decentralization of Education in Indonesia (Dewi, 2021). Thematic content analysis was applied to explore background issues, implementation strategies, and the challenges and implications of curriculum reform. The findings reveal a significant gap between policy and practice, as well as disparities in regional capacities that hinder effective reform. Strengthening synergy among curriculum design, teacher training, local institutional capacity, and adaptive evaluation is essential to ensure meaningful educational transformation in Indonesia. Keywords: curriculum reform, decentralization, Merdeka Curriculum